Optimization and comparison of heat and ultrasound assisted extraction techniques to obtain anthocyanin compounds from Arbutus unedo L. Fruits - Jiménez López, Cecília (2018)
The goal of this study was to compare anthocyanin extraction from Arbutus unedo L. fruits, by using two techniques assisted by different energy sources, heat and ultrasound. In order to obtain the conditions that maximize anthocyanin extraction, a response surface methodology was applied using the circumscribed central composite design of three variables with five levels. Three anthocyanin compounds were identified by HPLC-DAD-ESI/MS, being cyanidin-3-glucoside the main molecule. Heat assisted extraction proved to be the most effective method at 5 min, 90 °C and 80% of ethanol, yielding 51.2% of extract, with a total anthocyanin content of 382.4 μg/g dried fruit, and 744.6 μg/g extract. These response values were slightly improved by studying the solid/liquid effect at the optimal conditions in dose-response format, showing steady extraction values from 5 to 40 g/L. Results show the possibility of using A. unedo fruits as a source of anthocyanin compounds for industrial applications.